From real to virtual prism adaptation therapy: a systematic review on benefits and challenges of a new potential rehabilitation approach - Culicetto, Laura; Giustiniani, Andreina; Lo Buono, Viviana; Cazzato, Valentina; Falzone, Alessandra; Vicario, Carmelo Mario; Quartarone, Angelo; Marino, Silvia (Frontiers in Psychology, 2024)
Prism adaptation (PA) is a sensorimotor technique that has been shown to alleviate neglect symptoms. Due to its demonstrated functional effectiveness, PA has recently been implemented in virtual reality environments. However, research on virtual prism adaptation (VPA) is limited and it lacks a standardized methodological approach. It is crucial to investigate whether VPA can be effective in inducing traditional effect of PA and to have potential utility in a rehabilitation context. Clarifying this aspect would allow the use of VPA in a wider range of contexts and neurological disorders, with the additional opportunity to overcome PA traditional limits. The aim of the present study is to revise current literature on VPA in both healthy individuals and patients highlighting also its advantages and limitations. Studies performed between 2013 and 2023 and fulfilling the inclusion criteria were searched on three electronic databases, by combining the terms “Virtual prism adaptation” and “Virtual prism adaptation therapy. Out of 123 articles, only 16 met the inclusion criteria. The current literature review suggests that VPA may serve as a potentially useful tool for inducing visuomotor adaptation, with most studies conducted in healthy individuals. The high variability in the methodologies observed among studies suggests that more standardized approaches are needed to gain a deeper understanding of the mechanisms underlying adaptation and aftereffects when PA is administered in a virtual environment. Future studies should also address practical applications and clinical efficacy of VPA, particularly in patients with spatial neglect.